Smart and Intelligent Prayer System for Elderly Muslim with IoT - Mansor, Sarina; Azmi, Muhammad Nur Irham Firdaus; Ibrahim, Siti Azlida (International Journal of Integrated Engineering, 2024)
An assistive and monitoring prayer system has been designed to help elderly Muslims in performing their daily prayers. However, the system has several limitations in the aspect of efficiency, cost, size, complexity, security and usability. In this paper, several enhancements have been proposed to improve the existing smart prayer system including a better approach to retrieve exact prayer times, efficient way to retrieve current date/time, two different sensors used to detect the physical movements, smaller microcontroller with a built-in Wi-Fi module and the fabrication of PCB board. On the monitoring system, this project offers a more user’s friendly mobile application with several enhanced features. Reminder and authentication features are added to the mobile application for increased security and usability. The mobile application only allowed authorized or registered users to use the mobile application to view prayer performance of the elderly and send a prayer reminder to the elderly. The proposed system implements Internet of Things (IoT) technology, with a microcontroller communicating with the database through Wi-Fi, and data is modified before being displayed via the mobile application. Experimental testing shows a high level of support for the system's commercialization due to its ability to assist and monitor the elderly with their daily prayers. This new smart prayer system offers a more reliable assistive and monitoring system for elderly Muslim.